Intrigues [large type] - Lackey, Mercedes (Lackey, Mercedes. Collegium chronicles, 2010)
When Mag, an orphaned boy who was saved from slavery in the gem mines in his infancy, tracks down his parents' whereabouts, he unwittingly puts his own life in danger.